The Effect of CLWD-Flipped Classroom on Student Learning Outcomes: A Quasi-Experimental Study - Aminuddin Prahatama Putra; Nurul Hidayati Utami; Kaspul Kaspul (Jurnal Penelitian Pendidikan IPA, 2023)
Most teachers agree to implement LMS for learning Biology, but some of them still have difficulties. Most of them thought that LMS helped reduce learning loss after pandemic covid-19. One of them is using a Learning Management system (LMS). CLDW (Culture Literacy Digital Wetland) is one of the innovations as a learning for students. CLDW helps students and teachers improve their activities during online learning, such as discussions. A flipped classroom with a learning management system Systems-based flipped classrooms produce positive learning. CLDW-Flipped Classroom was designed in two phases, namely: first phase; out-of-class was marked by students using CLDW as teaching materials, and second phase; in-class was marked by conducting face-to-face learning in class The research used quasi-experimental research with a non-equivalent control group pretest-posttest design. The population of all students in 3 schools then consists of students in SMAN 4, SMAN 7, and MAN 2. The students are class X high school. Sampling was done by selecting two classes that were used as the control class and the experimental class. It is concluded that there is a significant effect on learning outcomes from integrating CLDW in the flipped classroom for learning biology. Overall, using CLDW-flipped classrooms has an effect on improving learning outcome. Flipped classrooms create effective classrooms through interaction with learners. Moving some aspects of the learning process to create extra time for active learning activities through teacher-led class discussions